1. Rozwiąż równania:
a) 10 a + 5 = 5 a + 20
b) 2 x -2(x+5) = X-8
c) 5 (x-1)-4 (x+3) - 5 = 3(x-2)
d) 4-[2-5(x + 1)] = 2
19-2x
2x-11
+
4
e)
2x
2​


Odpowiedź :

Odpowiedź:

a)

10a + 5 = 5a + 20

10a - 5a = 20 - 5

5a = 15 | :5

a = 3

b)

2x - 2(x + 5) = x - 8

2x - 2x - 10 = x - 8

-x = (-8) + 10

-x = 2 | * (-1)

x = -2

c)

5 (x - 1) - 4 (x + 3) - 5 = 3 (x - 2)

5x - 1 - (4x + 12) - 5 = 3x - 6

5x - 1 -4x - 12 - 5 = 3x - 6

5x - 4x - 3x = 1 + 12 + 5 - 6

-2x = 12 | : (-2)

x = 6

d)

4 - [2 - 5(x + 1)] = 2 * 19 - 2x - 11 + 4

4 - [2 -5x - 5] = 38 - 2x - 11 + 4

4 - 2 + 5x + 5 = 38 - 2x - 11 + 4

5x + 2x = 38 - 11 + 4 - 4 + 2 - 5

7x = 27 - 3

7x = 24 |:7

x = 3 i 3/7